Pengembangan Media Pembelajaran PAK Berbasis Android (MPBA) Kelas X SMA Negeri 2 Tarutung - Christofer Samosir; Elsina Sihombing; Liyus Waruwu (Institut Agama kristen Negeri Tarutung, 2022)
Abstract: The purpose of this study was to determine whether the MPBA developed was feasible to use. This research is research and development that is used to develop or validate products used in learning. The development model used by the researcher is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model which was modified by the researcher according to the needs to become ADDIED (Analysis, Planning, Design, Development, Implementation, Evaluation, Dissemination). The subjects of this research are one material expert, one media expert, one PAK subject teacher. The feasibility test can be observed in the questionnaire results obtained from testing by material experts with 21 indicators and 4 aspects, then the total score is 81 from a maximum score of 84 in the